Survival of Escherichia coli in the environment: fundamental and public health aspects - van Elsas, Jan Dirk (Nature Publishing Group, 2011)
In this review, our current understanding of the species Escherichia coli and its persistence in the open environment is examined. E. coli consists of six different subgroups, which are separable by genomic analyses. Strains within each subgroup occupy various ecological niches, and can be broadly characterized by either commensalistic or different pathogenic behaviour. In relevant cases, genomic islands can be pinpointed that underpin the behaviour. Thus, genomic islands of, on the one hand, broad environmental significance, and, on the other hand, virulence, are highlighted in the context of E. coli survival in its niches. A focus is further placed on experimental studies on the survival of the different types of E. coli in soil, manure and water. Overall, the data suggest that E. coli can persist, for varying periods of time, in such terrestrial and aquatic habitats. In particular, the considerable persistence of the pathogenic E. coli O157:H7 is of importance, as its acid tolerance may be expected to confer a fitness asset in the more acidic environments. In this context, the extent to which E. coli interacts with its human/animal host and the organism's survivability in natural environments are compared. In addition, the effect of the diversity and community structure of the indigenous microbiota on the fate of invading E. coli populations in the open environment is discussed. Such a relationship is of importance to our knowledge of both public and environmental health.